STRATEGI OMNICHANNEL DALAM PEMASARAN: DAMPAKNYA TERHADAP PEMASUKAN DAN KEBERLANJUTAN USAHA - Rolando, Benediktus; Simanjuntak, Enty Evasari; Dewi, Komala; Al-Amin, Al-Amin (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research investigates omnichannel strategies in marketing and their effects on increasing revenue and business sustainability. By reviewing relevant literature and case studies, this research identifies that the omnichannel approach, which integrates online and offline marketing channels to create a seamless customer experience, has a significant contribution to improving the financial performance and long-term sustainability of businesses. The findings show that an omnichannel strategy helps companies understand customer behavior more deeply, personalize offers, and increase customer satisfaction and loyalty. In addition, effective adaptation of information technology in support of omnichannel is proven to improve operational efficiency and strengthen the business's competitive position in the market. Thus, the implementation of an omnichannel strategy not only restructures the way companies interact with customers, but also plays an important role in strengthening the foundation of the business for future growth and sustainability. This research provides insights for business stakeholders on the importance of adopting and continuously updating omnichannel strategies to improve business performance and competitiveness.